Evaluación de la incorporación de microorganismos benéficos sobre la broza del cultivo de arroz (Oryza Sativa l.) variedad INIA - 507 realizado en la Estación Experimental El Porvenir - INIA - Juan Guerra - Saavedra Paredes, Michel (2009)
This research was conducted at the Agricultural Experimental Station "El Porvenir" - INIA - Juan Guerra, with the aim of evaluating the efficiency of three organic products, compared to conventional practices in the cultivation of rice (Oryza sativa L) seeking to demonstrate the efficiency of biological Bacthon, and Trichoderma Biospeed in crop production. Similarly, the experiment was adapted to design of a randomized complete block with six treatments and three replications. The work consisted of activities: preparation of the bed almaciguera, broadcast the seed at a rate of 80 Kg / Ha, a field transplantation final planting distance 25 x 25 cm. for all treatments, application of products Bacthon, and Trichoderma Biospeed to brush rice on T1, T2 and T3, and manual weeding. Intermittent irrigation was used and periodic flooding when required. Before beginning the work was conducted on soil analysis, just as was the climatic data of the area. Evaluations conducted during the growing period of the crop show that treatments T5 and T6 showed better development in plant height and number of tillers formed treatments T3 and T5. On the production side, the evaluations indicated that the treatments T3, T2 and T1 are given the best yields in grain, just as the economic analysis indicates that higher profitability was the treatment in question, having the highest performance T3 treatment and therefore more profitable crop. Regarding the incidence of Pyricularia grisea treatments T2 and T3 were less affected and Rizoctonia solani. treatments were the T3 and T4.